IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN KEUANGAN DESA - Megawati, Megawati; Usman, Jaelan; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of the research is to determine the implementation of good governance principles for financial management in Matampapole Village, Mallawa District, Maros Regency. This research uses a qualitative method with a descriptive type. Data collection techniques include observation, interviews and documentation. The results of the research show that there are five stages of principles of good governance in village financial management, namely equality which has done justice in informing the budget or financial management to the community, transparency has been transparent/open in conveying the budget or financial management to the community, accountability has been transparent/open in conveying the budget or financial management in the community, the effectiveness and efficiency of the community begins to feel efficient and changes in conveying the budget or financial management to the community and participation has carried out community consultation activities in conveying the budget or financial management to the community.